The effect of urban morphological characteristics on the spatial variation of PM2.5 air quality in downtown Nanjing. Issue 7 (2nd September 2021) - Kokkonen, Tom V.; Xie, Yuning; Paasonen, Pauli; Gani, Shahzad; Jiang, Lin; Wang, Bo; Zhou, Derong; Qin, Wei; Nie, Wei; Kerminen, Veli-Matti; Petäjä, Tuukka; Sun, Jianning; et al.
Abstract : The most important characteristics in terms of the PM2.5 concentrations were the fraction of trees and the height-normalized roughness length. The study was performed using continuous observations covering the whole scale of urban densities. Abstract : The effects of the urban morphological characteristics on the spatial variation of near-surface PM2.5 air quality were examined. Unlike previous studies, we performed the analyses in real urban environments using continuous observations covering the whole scale of urban densities typically found in cities. We included data from 31 measurement stations divided into 8 different wind sectors with individually defined morphological characteristics leading to highly varying urban characteristics. The urban morphological characteristics explained up to 73% of the variance in normalized PM2.5 concentrations in street canyons, indicating that the spatial variation of the near-surface PM2.5 air quality was mostly defined by the characteristics studied. The fraction of urban trees nearby the stations was found to be the most important urban morphological characteristic in explaining the PM2.5 air quality, followed by the height-normalized roughness length as the second important parameter. An increase in the fraction of trees within 50 m of the stations from 25 percentile to 75 percentile ( i.e. by the interquartile range, IQR) increased the normalized PM2.5 concentration by up to 24% in the street canyons. In open areas, an increase in the trees by the IQR actually decreased the normalized PM2.5 by 6% during the pre-COVID period. An increase in the height-normalized roughness length by the IQR increased the normalized PM2.5 by 9% in the street canyons. The results obtained in this study can help urban planners to identify the key urban characteristics affecting the near-surface PM2.5 air quality and also help researchers to evaluate how representative the existing measurement stations are compared to other parts of the cities.